2017
DOI: 10.1186/s12879-017-2357-1
|View full text |Cite
|
Sign up to set email alerts
|

Spatial, temporal and spatio-temporal clusters of measles incidence at the county level in Guangxi, China during 2004–2014: flexibly shaped scan statistics

Abstract: BackgroundOutbreaks of measles re-emerged in Guangxi province during 2013–2014, where measles again became a major public health concern. A better understanding of the patterns of measles cases would help in identifying high-risk areas and periods for optimizing preventive strategies, yet these patterns remain largely unknown. Thus, this study aimed to determine the patterns of measles clusters in space, time and space-time at the county level over the period 2004–2014 in Guangxi.MethodsAnnual data on measles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…Measles displayed a high-incidence season in spring, and mumps peak incidence occurred during the summer months with a peak of about half the size occurring in spring. Previous studies have revealed an association between the RIDs and seasons [18,22,30,36,37]. The occurrence of RIDs is related to climatic factors, such as the amount of sunshine, changes in the temperature, and indoor activity.…”
Section: Discussionmentioning
confidence: 99%
“…Measles displayed a high-incidence season in spring, and mumps peak incidence occurred during the summer months with a peak of about half the size occurring in spring. Previous studies have revealed an association between the RIDs and seasons [18,22,30,36,37]. The occurrence of RIDs is related to climatic factors, such as the amount of sunshine, changes in the temperature, and indoor activity.…”
Section: Discussionmentioning
confidence: 99%
“…This condition explains why some clusters are found in poor counties located in the western and northern parts of Guangxi, such as Jiangzhou, Xilin, and Luocheng. In addition, only a few children who migrate to the urban or suburban areas with their parents can timely receive free mumps vaccination [ 21 , 38 ]. Meanwhile, the current immunization strategies do not allow local children to develop high antibody concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Spatial scan statistics and Anselin's Moran I are widely used to detect spatial cluster for infectious disease (18,19). The strength of the scan statistic is that it can detect clusters over space and time.…”
Section: Discussionmentioning
confidence: 99%
“…However, some geographic units are sometimes included in both high-risk and low-risk clusters, this made it difficult to compare population density between high-and low-risk townships in our study. Anselin's Local Moran I is calculated for each geographic unit, therefore it is not sensitive to the shape of geographic features, and the detected clusters do not geographically overlap (19)(20)(21). Hence, we chose Anselin's Local Moran I to identify clusters of severe HFMD cases in our study.…”
Section: Discussionmentioning
confidence: 99%